The Good Cause Theoretical Perspectives on Corruption - de Graaf, Gjalt; von Maravic, Patrick; Waagenar, Pieter (Verlag Barbara Budrich, 2010)
Money makes the world go round - corruption The book presents the state of the art in studying the causes of corruption from a comparative perspective. Leading scholars in the field of corruption analysis shed light on the issue of corruption from different theoretical perspectives. Understanding how different theories define, conceptualize, and eventually deduce policy recommendations will amplify our understanding of the complexity of this social phenomenon and illustrate the spectrum of possibilities to deal with it analytically as well as practically.